2018
DOI: 10.1590/2317-1782/20182017164
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the linguistic profile in down syndrome using the arizona battery for communication disorders of dementia – a pilot study

Abstract: The ABCD battery is a useful tool in the evaluation of adults and elderly with DS and the performance of individuals in this battery correlates with indices of functionality. This is a pioneer study in Brazil, and it points to the need for a better characterization of the linguistic abilities of individuals with DS, in order to allow the elaboration of strategies that stimulate their communicative abilities as to promote greater social insertion for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In DS, attention deficits have been described in the early stages of AD [ 87 , 97 , 108 ], while in ADAD, attention deficits are observed in the preclinical phases of the disease [ 109 ]. With regard to language, in DS, there is already a major neurodevelopmental effect on expressive language, and cases of LOAD can also present with language deficits [ 110 ]. In fact, assessment of language skills could potentially help in identifying earlier DSAD [ 111 ].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In DS, attention deficits have been described in the early stages of AD [ 87 , 97 , 108 ], while in ADAD, attention deficits are observed in the preclinical phases of the disease [ 109 ]. With regard to language, in DS, there is already a major neurodevelopmental effect on expressive language, and cases of LOAD can also present with language deficits [ 110 ]. In fact, assessment of language skills could potentially help in identifying earlier DSAD [ 111 ].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…However, they were unable to define a cut-off score for screening dementia in people with severe intellectual disabilities. Carvalho et al 35 analyzed linguistic profile in DS using the Arizona Battery for Communication Disorders of Dementia (ABCD) and deemed the profile similar to that of individuals with Alzheimer disease. This was a pilot study based on a small sample (30 adults with DS) and the authors concluded that the investigation should be expanded to confirm the initial findings.…”
Section: Mental Healthmentioning
confidence: 99%